The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/myc.12017
|View full text |Cite
|
Sign up to set email alerts
|

Important aspects of oral paracoccidioidomycosis–a literature review

Abstract: Paracoccidioidomycosis is a deep mycosis endemic to Latin America, with considerable morbidity and mortality. It is caused by the dimorphic fungus Paracoccidioides brasiliensis, which affects, among other organs in the human body, the oral cavity. Fungus virulence and immunocompetence of the host determine the establishment of infection or active disease, whose severity and clinical behaviour depend mostly on the cellular immune response of the host. Often, oral lesions constitute the first sign and site of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 74 publications
(239 reference statements)
4
37
0
7
Order By: Relevance
“…According to gender and age we observed that PCM oral manifestations were more frequent in male patients, with 89.65% cases and age range of 41 to 62 years (75.85%), as it has been observed in earlier studies [5][6][7]. PCM oral manifestations occur at almost all ages, with highest incidence in ages between 30 and 50 years in its chronic form (adult type), which is the most common in 90% of the cases, with classic signs and symptoms that include pulmonary and mucosal involvement [5,6].…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…According to gender and age we observed that PCM oral manifestations were more frequent in male patients, with 89.65% cases and age range of 41 to 62 years (75.85%), as it has been observed in earlier studies [5][6][7]. PCM oral manifestations occur at almost all ages, with highest incidence in ages between 30 and 50 years in its chronic form (adult type), which is the most common in 90% of the cases, with classic signs and symptoms that include pulmonary and mucosal involvement [5,6].…”
Section: Discussionsupporting
confidence: 70%
“…In this study it was found 10.34% of prevalence; in contrast, some researchers do not report any case of HIV/AIDS coinfection [6]. Therefore, the dentist should always suspect immunosuppression in patients with PCM or histoplasmosis oral manifestations, due to the fact that these mycoses can be AIDS/HIV-defining illnesses [1,5,10,11,17,19].…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations